Trading Blocs and Welfare : How Trading Bloc Members Are Affected by New Entrants - Hacker, R. (IMF Working Papers; Working Paper ;, 1998)
This paper uses the three-country duopoly model to examine the effects of lowered trade barriers when a new entrant joins a trading bloc. There are two firms-a small-country firm and a large-country firm within the bloc-and three markets-two within and one (new entrant's) outside the bloc. The analysis generally shows greater gains for the small-country than for the large-country firm. The small-country firm will export more to the external country than the large-country firm. But if tariffs decline, the export share of the large-country firm will increase relative to the small-country firm's, though profits will improve more for the latter.